The new imaging findings: "Passing spine" without kissing. Issue 22 (4th June 2021) - Kasai, Yuichi; Mizuno, Tetsutaro; Paholpak, Permsak; Sirichativapee, Winai; Fukui, Mitsuru
Abstract : Abstract: Case-control studies by examining the lumbar spine computed tomography (CT) findings focusing on the spinous processes. "Passing spine" was defined as a lumbar degenerative change observed on CT images. In contrast, kissing spine, which is also an image finding, has been acknowledged as an established clinical condition. Therefore, we compared the passing spine group and the kissing spine group to investigate whether the 2 groups belong to a similar disease group; this would help explain the clinical and imaging characteristics of patients with passing spine. Previous studies have described the gradual increase in the height and thickness of the lumbar vertebral spinous processes that can occur in individuals aged >40 years, and reported that this progressive degeneration can lead to a condition termed "kissing spine." We examined the CT imaging of 373 patients with lumbar spinal disease and divided patients into 2 groups, the kissing spine (K) group and the passing spine (P) group, and compared the clinical (age, sex, presence/absence of lower extremity pain) and imaging data (localization of kissing or passing spine, intervertebral disc height at the level of kissing or passing spine, lumbar lordosis (LL) angle, presence/absence of vacuum phenomenon (VP) in the intervertebral discs and spondylolisthesis at the level of kissing or passing spine between the 2 groups. Compared with patients with kissing spine, patients with passing spine had an increased incidence of lower extremity pain, lower intervertebral disc height at the level of passing spine, relatively static LL, and VP commonly observed in the intervertebral discs at the level of passing spine. Because the clinical and imaging characteristics of patients with passing spine are different from those of patients with kissing spine, passing spine might be a pathological condition distinct from kissing spine.